2021
DOI: 10.1007/s00423-021-02105-z
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Hybrid-NOTES procedures—do they have a negative impact on pregnancy and delivery?

Abstract: Purpose We conducted a retrospective observational study in order to identify negative effects of NOTES procedures (Natural Orifice Transluminal Endoscopic Surgery) with transvaginal specimen removal on pregnancy and delivery. Methods From the total population of 299 patients in our NOTES registry, we tried to contact the 121 patients who were of reproductive age (≤ 45 years) at the time of a transvaginal NOTES procedure. They were interviewed by telephone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…19,20 Regarding the impact of vNOTES on childbirth, several cases of successful vaginal delivery among patients who underwent the first vNOTES, including ovarian cystectomy, tubal ligation, and myomectomy, have been reported, primarily revealing the relative safety of vNOTES concerning childbirth. 21,22 However, no evidence of the impact of repeated vNOTES on childbirth has been reported in the literature. Unfortunately, due to the relatively short postoperative follow-up period and small cohort size in our study, after the second vNOTES, none of the patients had delivered vaginally or via cesarean section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Regarding the impact of vNOTES on childbirth, several cases of successful vaginal delivery among patients who underwent the first vNOTES, including ovarian cystectomy, tubal ligation, and myomectomy, have been reported, primarily revealing the relative safety of vNOTES concerning childbirth. 21,22 However, no evidence of the impact of repeated vNOTES on childbirth has been reported in the literature. Unfortunately, due to the relatively short postoperative follow-up period and small cohort size in our study, after the second vNOTES, none of the patients had delivered vaginally or via cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of vNOTES on childbirth, several cases of successful vaginal delivery among patients who underwent the first vNOTES, including ovarian cystectomy, tubal ligation, and myomectomy, have been reported, primarily revealing the relative safety of vNOTES concerning childbirth 21,22 . However, no evidence of the impact of repeated vNOTES on childbirth has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we are concerned about the possible long-term effects of vNOTES on vaginal delivery in term pregnancies. It has been reported that full-term delivery can lead to rupture of the vaginal vault ( 13 ), but whether vNOTES will receive long-term benefits on vaginal delivery of full-term pregnancy and female sexual function has been less reported ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“… 28 Regarding pregnancy, very recent data exist showing that future pregnancies are not affected by NOTES procedures. 29 …”
Section: Discussionmentioning
confidence: 99%
“…28 Regarding pregnancy, very recent data exist showing that future pregnancies are not affected by NOTES procedures. 29 Women less than 40 years are less likely to choose the transvaginal cholecystectomy. This connection between younger as well as nulliparous women and their cautious acceptance for transvaginal NOTES is also reported by other authors.…”
Section: Dovepressmentioning
confidence: 99%